My mother's or my own?case studies on selected mothers' experiences on received perenting style and its influences on their present parenting - Fiona Christy, Anthony Oswin (University Malaysia Sarawak, (UNIMAS), 2007)
This research will be discussing precisely on the parenting experiences selected mothers had during their youth. Often people did not stop and listen to the reason for a person to do something. Realizing the importance of parenting role especially in handling their teenage daughter in today's world, this research trying to explore the experiences that selected mother had gone through and how that had impacted on them.